PENGARUH EFIKASI DIRI, KEPUASAN KERJA DANPERSEPSI TENTANG JABATAN TERHADAP KINERJA KEPALA SMK NEGERI DI PROVINSI DKI JAKARTA - DARWIN, DARWIN (JURNAL ILMIAH EDUCATIONAL MANAGEMENT, 2011)
The objective of this research is to confirmÂ  the effectÂ  of self-efficacy, job satisfaction and perception about position on principalsâ performance of state vocational senior secondary school in Jakarta Province. This research was conducted in Jakarta. The data had been analyzed using path analysis. The populations of this research were 61 principals are there in six city/districts. The questioners of this research had been testing on the 21 principals. Therefore, by proportional random sampling the samples of this research were 40 principals which were selected proportionally and randomly.The research findings are as follows: (1) there was a positive direct effect of self-efficacy on principalsâ performance, (2) there was a positive direct effect of job satisfaction on principalsâ performance, (3) there was a positive direct effect of perception about position on principalsâ performance, (4) there was a positive direct effect of self-efficacy on job satisfaction, and (5) there was a positive direct effect of self-efficacy on perception about position.Keywords: School principalâs performance, self efficacy, job satisfaction, perception about position.